Sleep Stage Transitions in Healthy Humans Altered by Central Monoaminergic Antagonist - Kishi, A.; Yasuda, H.; Matsumoto, T.; Inami, Y.; Horiguchi, J.; Struzik, Z. R.; Yamamoto, Y. (Methods of Information in Medicine, 2010)
Objectives: Sleep stage transitions constitute one of the key components of the dynamical aspect of sleep. However, neural mechanisms of sleep stage transitions have not, to date, been fully elucidated. We investigate the effects of administrating risperi-done, a central serotonergic and dopaminergic antagonist, on sleep stage transitions inhumans, and also on ultradian rapid-eye-movement (REM) sleep rhythms.Methods: Ten healthy young male volunteers (age: 22 ± 3.7 years) participated in this study. The subjects spent three nights in a sleep laboratory. The first was the adaptation night, and the second was the baseline night. On the third night, the subjects received risperidone (1 mg tablet) 30 min before the polysomnography recording. We measured and investigated transition probabilities between waking, REM and non-REM (stages I–IV) sleep stages.Results: We found that the probability of transition from stage II to stage III was significantly greater for the risperidone night than for the baseline night. We also found that risperidone administration prolonged REM-onset intervals, when compared to the baseline night.Conclusions: We demonstrate that central serotonergic and /or dopaminergic neural transmissions are involved in the regulation of sleep stage transitions from light (stage II) to deep (stage III) sleep, and also in determining ultradian REM sleep rhythms.
Keywords: Dopamine; REM-onset interval; risperidone; serotonin; sleep stage transitions